2000
DOI: 10.1034/j.1399-0012.2000.140111.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of renal transplant recipients with pneumococcal polysaccharide vaccine

Abstract: Pneumococcal vaccination is safe and effective in patients with well-functioning renal allografts, at least in the short term. This vaccination policy may be useful for preventing invasive pneumococcal disease in immunosuppressed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 17 publications
0
17
0
2
Order By: Relevance
“…On the other hand, patients on dialysis had greater pre-and postvaccination titers than renal recipients, although both groups reached protective antibody titers after vaccination (72). However, this protection appears to be only short-term in renal recipients (60), and functional opsonic antibodies were significantly lower in these patients compared to controls (10).…”
Section: Pneumococcal Vaccinementioning
confidence: 82%
“…On the other hand, patients on dialysis had greater pre-and postvaccination titers than renal recipients, although both groups reached protective antibody titers after vaccination (72). However, this protection appears to be only short-term in renal recipients (60), and functional opsonic antibodies were significantly lower in these patients compared to controls (10).…”
Section: Pneumococcal Vaccinementioning
confidence: 82%
“…Kazancioglu et al (82) , estudando prospectivamente 21 pacientes com transplante renal funcionante, observaram que a vacinação pneumocócica não provocou efeitos adversos sistêmicos ou locais. A mesma foi eficaz, levando a aumento significativo dos títulos de anticorpos seis e 12 semanas após a vacinação, em todos os pacientes exceto um.…”
Section: J Pneumol 27(2) -Mar-abr De 2001unclassified
“…Each dose of 0.5 mL contains purified S. pneumoniae polysaccharides (PS), 25 µg of each of the included 23 serotypes (Rybachenko et al, 2009). Although pneumo-23 is composed of non-T cell-dependent polysaccharides, it was observed that pneumo-23 vaccine when is given to elderly people, or immunosuppressed patients, their immune response, in unexplained manner, was moderately enhanced non-specifically in addition to the immune protection achieved against pneumococcal infection (Rybachenko et al, 2009;vad der Harst, 2007;Kazancioglu et al, 2000). In addition, a recent study revealed another immune enhancing feature of pneumo-23 vaccine stating that pneumo-23 vaccine enhanced the opsonization and sustained normal compliment components of C3 and C4 in elderly cancer patients after splenectomy Uslu et al, 2006).…”
Section: Model Study For the Experimentally Zwitterionized Bacterial mentioning
confidence: 99%
“…This vaccine was designed mainly to confer immunity against severe pneumococcal infections in elderly patients and those who underwent splenectomy as part of a management of various hematological disorders, renders the patients unsusceptible to the development of overwhelming sepsis by Streptococcus pneumoniae (Pasteur Merieux Connaught, 2004;Rybachenko et al, 2009;vad der Harst, 2007;Kazancioglu et al, 2000). Pneumo-23 is a clear, colorless liquid prepared from purified pneumococcal capsular antigens.…”
Section: Model Study For the Experimentally Zwitterionized Bacterial mentioning
confidence: 99%